Artocarpus tonkinensis Protects Mice Against Collagen-Induced Arthritis and Decreases Th17 Cell Function - Adorisio, Sabrina; Fierabracci, Alessandra; Muscari, Isabella; Liberati, Anna Marina; Calvitti, Mario; Cossignani, Lina; Blasi, Francesca; Quan, Tran Duc; Tam, Nguyen Thanh; Sung, Tran Van; Riccardi, Carlo; Thuy, Trinh Thi; et al. (Frontiers in Pharmacology, 2019)
Artocarpus tonkinensis is a tree that grows in north Vietnam whose leaf decoction is used as a traditional remedy by the Hmong ethnic group to treat arthritis and backache. Our study evaluated the decoction’s efficacy and mechanism of action in DBA/1J mice with collagen-induced arthritis (CIA). Mice treated with the decoction (At) either from the first collagen immunization or after CIA development experienced significantly less joint edema and inflammatory infiltration, whereas CIA-induced cartilage damage could only be prevented by early At treatment. Autoimmune gene expression profiles showed that Th17 cell-associated chemokine CCL20 and cytokines IL-6, IL-17, and IL-22 were strongly downregulated by At. Reduced expression of IL-2, IL-17, IL-22, and FasL in lymph node cells from At-treated mice was further confirmed by real-time PCR. The decoction also inhibited polarization of Th17 cells from CD4+ splenic T cells according to levels of IL-17 and RORC, a Th17 cell-specific transcription factor. Chromatographic analysis identified At’s major component as maesopsin-β-D-glucoside, which could inhibit in vitro differentiation of Th17 cells. The decoction significantly alleviated the signs and symptoms of CIA and inhibited the development and function of Th17 cells, highlighting its potent anti-inflammatory activity.